2
$\begingroup$

this series was evaluated by Cornel Valean here using series manipulation.

I took a different path as follows:

using the identity:$$\frac{\ln^2(1-x)}{1-x}=\sum_{n=1}^\infty x^n\left(H_n^2-H_n^{(2)}\right)$$ multiply both sides by $\ln^3x/x$ then integrate

$$-6\sum_{n=1}^\infty \frac{H_n^2-H_n^{(2)}}{n^4}=\int_0^1\frac{\ln^2(1-x)\ln^3x}{x(1-x)}\ dx$$ I was able here to find \begin{align} \sum_{k=1}^\infty\frac{H_k^{(2)}}{k^4}&=\frac43\zeta^2(3)-\frac23\sum_{k=1}^\infty\frac{H_k^{(3)}}{k^3}\\ &=\zeta^2(3)-\frac13\zeta(6) \end{align} as for the integral, it seems very tedious to calculate it using the derivative of beta function.

can we find it with or without using beta function?

$\endgroup$
  • $\begingroup$ By 'as for the integral', do you mean $\int_0^1\frac{\ln^2(1-x)\ln^3x}{x(1-x)}\ dx$ which equals to $[\frac{\ln^6 x}{6}]_0^1$? $\endgroup$ – Toby Mak Jun 2 at 6:08
  • $\begingroup$ @TobyMak how's that? That integral is not easy to calculate using beta function. $\endgroup$ – Ali Shather Jun 2 at 6:36
  • $\begingroup$ You cannot compute the integral since at $x=0$ the integral does not converge. $\endgroup$ – Toby Mak Jun 2 at 12:03
  • $\begingroup$ Using the derivative of the Beta function seems to be the clearer way. Anyway have you tried to split into two integrals with partial fraction? One has: $$\int_0^1 \frac{\ln^2(1-x)\ln^3 x}{x}dx=-12\sum_{n=1}^\infty \frac{H_n}{(n+1)^5}$$ $\endgroup$ – LeBlanc Jun 2 at 15:24
  • $\begingroup$ @ykcaZ yes I tried but the second integral is tough too. $\endgroup$ – Ali Shather Jun 2 at 15:32
2
$\begingroup$

This solution is by Cornel Valean.

Using the follwing identity: ( see Lemma $2(b)$ in this paper) $$\int_0^1x^{n-1}\ln^2(1-x)\ dx=\frac{H_n^2+H_n^{(2)}}{n}$$ and since $$\int_0^1x^{n-1}\ln^2(1-x)\ dx=2\sum_{k=1}^\infty\frac{H_{k-1}}{k}\int_0^1x^{n+k-1}\ dx=2\sum_{k=1}^\infty\frac{H_{k-1}}{k(n+k)}$$ Then $$\sum_{k=1}^\infty\frac{H_{k-1}}{k(n+k)}=\frac{H_n^2+H_n^{(2)}}{2n}\tag{1}$$ Divide both sides by $n^3$ then sum both sides from $n=1$ to $\infty$, we get \begin{align} S&=\color{blue}{\frac12\sum_{n=1}^\infty\frac{H_n^2}{n^4}+\frac12\sum_{n=1}^\infty\frac{H_n^{(2)}}{n^4}}=\sum_{k=1}^\infty\frac{H_{k-1}}{k}\left(\sum_{n=1}^\infty\frac{1}{n^3(n+k)}\right)\\ &=\sum_{k=1}^\infty\frac{H_{k-1}}{k}\left(\sum_{n=1}^\infty\left[\frac{1}{k^3}\left(\frac{1}{n}-\frac{1}{n+k}\right)-\frac1{n^2k^2}+\frac1{n^3k}\right]\right)\\ &=\sum_{k=1}^\infty\left(\frac{H_k}{k}-\frac{1}{k^2}\right)\left(\frac{H_k}{k^3}-\frac{\zeta(2)}{k^2}+\frac{\zeta(3)}{k}\right)\\ &=\sum_{k=1}^\infty\frac{H_k^2}{k^4}-\sum_{k=1}^\infty\frac{H_k}{k^5}-\zeta(2)\sum_{k=1}^\infty\left(\frac{H_k}{k^3}-\frac1{k^4}\right)+\zeta(3)\sum_{k=1}^\infty\left(\frac{H_k}{k^2}-\frac1{k^3}\right)\\ &=\sum_{k=1}^\infty\frac{H_k^2}{k^4}-\left(\frac74\zeta(6)-\frac12\zeta^2(3)\right)-\zeta(2)\left(\frac14\zeta(4)\right)+\zeta(3)\left(\zeta(3)\right)\\ &=\color{blue}{\sum_{k=1}^\infty\frac{H_k^2}{k^4}-\frac{35}{16}\zeta(6)+\frac32\zeta^2(3)} \end{align} Rearranging the blue sides, we get

$$\sum_{k=1}^\infty\frac{H_k^2}{k^4}=\frac{35}{8}\zeta(6)-3\zeta^2(3)+\sum_{k=1}^\infty\frac{H_k^{(2)}}{k^4}\\ =\frac{97}{24}\zeta(6)-2\zeta^2(3)$$

where we used $\ \displaystyle\sum_{k=1}^\infty\frac{H_k^{(2)}}{k^4}=\zeta^2(3)-\frac13\zeta(6)\ $ (can be found in the same paper I linked or here)

$\endgroup$
1
$\begingroup$

For a slight variation on a theme.

As $$\int_0^1 x^{n - 1} \ln^2 (1 - x) \, dx = \frac{H^2_n}{n} + \frac{H^{(2)}_n}{n},$$ for a proof of this result, see here, we can write the sum as \begin{align} \sum_{n = 1}^\infty \frac{H^2_n}{n^4} &= \sum_{n = 1}^\infty \frac{1}{n^3} \cdot \frac{H^2_n}{n}\\ &= - \sum_{n = 1}^\infty \frac{H^{(2)}_n}{n^4} + \int_0^1 \frac{\ln^2 (1 - x)}{x} \sum_{n = 1}^\infty \frac{x^n}{n^3} \, dx\\ &= - \sum_{n = 1}^\infty \frac{H^{(2)}_n}{n^4} + \int_0^1 \frac{\ln^2 (1 - x) \operatorname{Li}_3 (x)}{x} \, dx.\tag1 \end{align} Making use of the following Maclaurin series expansion for $\ln^2 (1 - x)$, namely $$\ln^2 (1 - x) = 2 \sum_{n = 1}^\infty \frac{H_n x^{n + 1}}{n + 1},$$ the integral in (1) can be re-written as \begin{align} \sum_{n = 1}^\infty \frac{H^2_n}{n^4} &= - \sum_{n = 1}^\infty \frac{H^{(2)}_n}{n^4} + 2 \sum_{n = 1}^\infty \frac{H_n}{n + 1} \underbrace{\int_0^1 x^n \operatorname{Li}_3 (x) \, dx}_{\text{IBP 3 times}}\\ &= - \sum_{n = 1}^\infty \frac{H^{(2)}_n}{n^4} + 2 \sum_{n = 1}^\infty \frac{H_n}{n+ 1} \left [\frac{\zeta (3)}{n + 1} - \frac{\zeta (2)}{(n + 1)^2} + \frac{H_{n + 1}}{(n + 1)^3} \right ]\\ &= - \sum_{n = 1}^\infty \frac{H^{(2)}_n}{n^4} + 2 \zeta (3) \underbrace{\sum_{n = 1}^\infty \frac{H_n}{(n + 1)^2}}_{n \, \mapsto \, n - 1} -2 \zeta (2) \underbrace{\sum_{n = 1}^\infty \frac{H_n}{(n + 1)^3}}_{n \, \mapsto \, n - 1} + 2 \underbrace{\sum_{n = 1}^\infty \frac{H_n H_{n + 1}}{(n + 1)^2}}_{n \, \mapsto \, n - 1}\\ &= - \sum_{n = 1}^\infty \frac{H^{(2)}_n}{n^4} + 2 \zeta (3) \sum_{n = 1}^\infty \frac{1}{n^2} \left (H_n - \frac{1}{n} \right ) - 2 \zeta (2) \sum_{n = 1}^\infty \frac{1}{n^3} \left (H_n - \frac{1}{n} \right )\\ & \qquad + 2 \sum_{n = 1}^\infty \frac{H_n}{n^4} \left (H_n - \frac{1}{n} \right )\\ &= - \sum_{n = 1}^\infty \frac{H^{(2)}_n}{n^4} + 2 \zeta (3) \sum_{n = 1}^\infty \frac{H_n}{n^2} - 2 \zeta^2 (3) - 2 \zeta (2) \sum_{n = 1}^\infty \frac{H_n}{n^3} + 2 \zeta (2) \zeta (4)\\ & \qquad + 2 \sum_{n = 1}^\infty \frac{H^2_n}{n^4} - 2 \sum_{n = 1}^\infty \frac{H_n}{n^5}\\ \Rightarrow \sum_{n = 1}^\infty \frac{H^2_n}{n^4} &= \sum_{n = 1}^\infty \frac{H^{(2)}_n}{n^4} - 2 \zeta (3) \sum_{n = 1}^\infty \frac{H_n}{n^2} + 2 \zeta (2) \sum_{n = 1}^\infty \frac{H_n}{n^3} + 2 \sum_{n = 1}^\infty \frac{H_n}{n^5}\\ & \qquad + 2 \zeta^2 (3) - 2 \zeta (2) \zeta (4).\tag2 \end{align}

Making use of the following results: \begin{align} \sum_{n = 1}^\infty \frac{H_n}{n^2} &= 2 \zeta (3)\\ \sum_{n = 1}^\infty \frac{H_n}{n^3} &= \frac{5}{4} \zeta (4)\\ \sum_{n = 1}^\infty \frac{H_n}{n^5} &= -\frac{1}{2} \zeta^2 (3) + \frac{7}{4} \zeta (6)\\ \sum_{n = 1}^\infty \frac{H^{(2)}_n}{n^4} &= \zeta^2 (3) - \frac{1}{3} \zeta (6)\\ \zeta (2) \zeta (4) &= \frac{7}{6} \zeta (6) \end{align} substituting into (2) leads to $$\sum_{n = 1}^\infty \frac{H^2_n}{n^4} = \frac{97}{24} \zeta (6) - 2 \zeta^2 (3),$$ as desired.

$\endgroup$
  • $\begingroup$ Nice... I missed this approach. $\endgroup$ – Ali Shather Jul 17 at 4:11
  • $\begingroup$ Its more convenient to write $$\ln^2(1-x)=2\sum_{n=1}^\infty\left(\frac{H_n}{n}-\frac{1}{n^2}\right)x^n$$ and this way we can avoid the annoying expression of $n+1$. $\endgroup$ – Ali Shather Jul 17 at 4:24
  • $\begingroup$ @Ali Shather - Yes, I agree writing $\ln^2 (1 - x)$ that way would be more convenient. Nice observation. $\endgroup$ – omegadot Jul 17 at 4:27
  • 1
    $\begingroup$ I always write it that way if you notice my solutions. by the way, we can apply the same two approaches to find $\sum_{n=1}^\infty \frac{H_n^2}{n^5}$ as its easy to compute $\sum_{n=1}^\infty \frac{H_n^{(2)}}{n^5}=5\zeta(2)\zeta(5)+2\zeta(3)\zeta(4)-10\zeta(7)$ $\endgroup$ – Ali Shather Jul 17 at 4:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.